STRATEGI GURU DALAM MENGEMBANGKAN INSTRUMEN BERBASIS HIGH ORDER THINKING SKILL PADA MATA PELAJARAN BAHASA INDONESIA - Septiana, Nyangfah Nisa; Shaleh, Shaleh; Zulfahmi, Zufahmi; Khoiriyah, Zulfatul (STKIP Persada Khatulistiwa Sintang, 2025)
Teachers’ strategies in developing High Order Thinking Skills (HOTS)-based instruments are essential in responding to the advancement of knowledge and in producing highly competent students. This study aims to describe teachers’ strategies in developing HOTS-based assessment instruments in Indonesian language subjects. The research employed a qualitative approach with a case study method. Data were collected through interviews with three (3) participants. Data analysis was conducted in three (3) stages: data condensation, data display, and conclusion drawing. The results show that teachers' strategies in developing HOTS-based questions include: 1) analyzing the core competencies (KD), 2) determining the learning objectives to be achieved, 3) designing the test blueprint by identifying the HOTS-related KD, formulating achievement indicators, selecting appropriate materials, formulating item indicators, determining the HOTS cognitive level based on Bloom’s taxonomy, and developing multiple-choice or essay questions, 4) choosing contextual stimuli to introduce the questions, 5) writing items based on the blueprint, 6) preparing answer keys, and 7) analyzing validity, reliability, difficulty level, and item discrimination. The implications of the study suggest that it can serve as a reference for teachers in designing HOTS-based assessment instruments.